2015
DOI: 10.1021/acsami.5b04572
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophilic Carboxyl Cotton Chelator for Titanium(IV) Immobilization and Its Application as Novel Fibrous Sorbent for Rapid Enrichment of Phosphopeptides

Abstract: Sample preparation methods with high selectivity, efficiency, and matrix resistance are essential for phosphoproteomic analysis. In this study, carboxyl cotton chelator-titanium(IV) (CCC-Ti4+) fibers, a novel CCC-based fibrous sorbent with excellent biocompatibility, were successfully synthesized on the basis of the coordination effect between double carboxyl groups on CCC and Ti4+. The synthesis of CCC-Ti4+ fibers was easy, and the incorporated titanium content was high. On the basis of immobilized metal ion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 57 publications
(30 citation statements)
references
References 41 publications
2
28
0
Order By: Relevance
“…However, in previous report, the synthesis of the bicyclic 2‐pyridone derivatives is somehow complicated . As illustrated in Scheme , in this study, the supposed formation processes for the formation of the nonaromatic molecule involved five steps: amidation, nucleophilic addition, dehydroxylation, cyclization reaction, and dehydroxylation, resulting in the nonaromatic structure of 5‐oxo‐2,3‐dihydro‐5 H ‐(1,3)thiazolo(3,2‐a)pyridine‐3,7‐dicarboxylic acid (noted as TPA), as similar to the mechanism reported by Kasprzyk and co‐workers . In their pioneering work, the solvent of water was removed from the CA+Cys aqueous mixture under vacuum and then the mixture was heated at high temperature (180 °C), resulting in a crude product that contains TPA .…”
Section: Resultsmentioning
confidence: 77%
“…However, in previous report, the synthesis of the bicyclic 2‐pyridone derivatives is somehow complicated . As illustrated in Scheme , in this study, the supposed formation processes for the formation of the nonaromatic molecule involved five steps: amidation, nucleophilic addition, dehydroxylation, cyclization reaction, and dehydroxylation, resulting in the nonaromatic structure of 5‐oxo‐2,3‐dihydro‐5 H ‐(1,3)thiazolo(3,2‐a)pyridine‐3,7‐dicarboxylic acid (noted as TPA), as similar to the mechanism reported by Kasprzyk and co‐workers . In their pioneering work, the solvent of water was removed from the CA+Cys aqueous mixture under vacuum and then the mixture was heated at high temperature (180 °C), resulting in a crude product that contains TPA .…”
Section: Resultsmentioning
confidence: 77%
“…Experimental results showed that the developed lab‐in‐syringe SPE approach allowed rapid and effective enrichment in less than 3 min without any electrical device. Subsequently, Feng and co‐workers applied the lab‐in‐syringe SPE technology with various adsorbents for proteomics researches, further verifying the simplified procedure and short extraction time of the proposed method .…”
Section: Introductionmentioning
confidence: 84%
“…In the extraction process, the sample solution and eluent are repeatedly passed through the adsorbent through pulling and pushing the plunger of syringe for several cycles, and in this way the extraction procedures including loading, washing, and eluting can be easily performed. The in‐syringe SPE technology has realized its own value in biological analysis . Feng synthesized the silica fiber with highly ordered mesoporous structure and continuously long fibrous property, and developed a lab‐in‐syringe SPE system using the prepared silica fiber as adsorbent for the enrichment of endogenous peptides from biological samples .…”
Section: Introductionmentioning
confidence: 99%
“…Such direct detection of S-linked phosphorylation seems suitable for less complex analytes, such as in the case of offline fractionation (Ruprecht et al 2017) or affinity enrichment procedures. In preliminary experiments, S-phosphopeptides from a sample of Digest 1 were enriched using a hydrophilic Ti-IMAC (He et al 2015) prepared in-house from cotton-wool. The enriched analyte was subjected to a series of tandem MS applying complementary fragmentation methods CID, HCD, ETD, ETciD, and EThcD [S12].…”
Section: Direct Detection Of S-linked Phosphorylationmentioning
confidence: 99%